2001
DOI: 10.1054/bjoc.2001.2023
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting reduction of risk of colorectal cancer following screening endoscopy

Abstract: Several studies have suggested that incidence and mortality of colorectal cancer (CRC) may be strongly reduced for up to 10 years by endoscopic screening with removal of precancerous lesions, but so far there are no data on risk reduction beyond this period. We assessed long-term reduction of CRC risk following screening endoscopy in a statewide population-based case-control study in Saarland, Germany. Lifetime history of screening endoscopy was compared between 320 cases with CRC aged 45-80 and 263 controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0
17

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 26 publications
5
31
0
17
Order By: Relevance
“…Our results are consistent with and extend previous findings of risk reduction of CRC after colonoscopy, which were either based on much smaller numbers of case patients (3,8,9,20) or relied on administrative claims (14). In particular, our results corroborate the evidence that colonoscopy may also substantially reduce CRC incidence in the community setting, and they suggest that this risk reduction may be stronger than shown by previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with and extend previous findings of risk reduction of CRC after colonoscopy, which were either based on much smaller numbers of case patients (3,8,9,20) or relied on administrative claims (14). In particular, our results corroborate the evidence that colonoscopy may also substantially reduce CRC incidence in the community setting, and they suggest that this risk reduction may be stronger than shown by previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The effectiveness of colonoscopy in preventing CRC is less clear in the community setting. Observational studies conducted in the community setting (and not restricted to specialized centers) have indicated a reduction of CRC incidence and mortality after colonoscopy, albeit to a much lesser extent (3)(4)(5)(6)(7)(8)(9), possibly because colorectal adenomas may be missed more frequently in such settings (10 -13). Furthermore, recent studies suggest that risk reduction mainly affects or may even be restricted to the left colon and rectum, whereas risk reduction in the right colon remains uncertain (14,15).…”
mentioning
confidence: 99%
“…Our estimates of the proportion of colorectal cancer that might be prevented by colonoscopy are in line with previous studies from the United States (14), Germany (15), and Italy (16). An even stronger risk reduction had been observed in the United States National Polyp Study (17).…”
Section: Discussionsupporting
confidence: 91%
“…Similar predominance of distal location has been reported for colorectal adenomas and colorectal carcinomas (20). The finding of particularly strong risk reduction for distal colorectal cancer is consistent with results of previous studies (14,15,21,22), including a very large case-control study from the United States (23).…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have suggested that the "protective effect" of a negative SC in terms of decreased CRC mortality lasts for more than 10 years [33][34][35][36][37] . Based on estimates from this literature, we reduced the CRC mortality rate by 50% and replicated the analysis to estimate how these patients would benefit from SC.…”
Section: Estimating the Colorectal Cancer-attributable Risk Of Deathmentioning
confidence: 99%